The Designing of Villa in Tourist Area Sipiso-Piso - Firman Eddy; Amanda Yasmine D. Matondang (International Journal of Architecture and Urbanism, 2020)
Villa is a facility lodging that is not only used for resting during leisure or recreation but also requirements for means of gathering places and deliberations (meetings) with providing room service and meeting rooms. Sipiso-Piso is the name of the famous waterfall that is in Karo’s land. Sipiso-Piso Villa provided to tourists who want to stay in the Sipiso-Piso area and to feels and enjoy the view from Toba Lake and the nature of the hills and Sibuatan Mount. It has four types of villas expected to hold different quantities of tourists. This villa also to accommodate MICE activity when in works days. It has facilities support, which is a restaurant, jogging track, and park. Each type has its private pool. This villa adopted tropical architecture. Thermal comfort is the most aspect of this theme.